Исследование возможности создания газоанализатора с транзисторным чувствительным элементом - Murshudli, M. M.; Alieva, A. M.; Musaev, M. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The possibility of creating a gas analyzer based on an n-p-n bipolar transistor operating in the self-oscillation mode is considered. Within the operating temperature range from –20 to +50 °C and for NOx concentrations of 5–500 ppm, the dependence of oscillation frequency on concentration is linear. The detection capability is at the level of 3–5 ppm. The gas analyzer allows measurement of nitrogen oxide concentration within a few seconds. Structurally, it is designed as a compact device with dimensions of 150×85×25 mm.